Numerical investigation of heat transfer and flow characteristics of MHD nano-fluid forced convection in a pipe - Erdem, Murat; Varol, Yasin (Springer, 2020)
In this study, the behavior of Cu-water nano-fluid in a pipe has been investigated numerically. The pipe is under the external magnetic field, and the magnetic field is applied perpendicularly to the pipe. The temperature of pipe is higher than the temperature of fluid. The study was carried out for three different Reynolds numbers. The magnetic field forces and nano-fluid volume fractions were chosen as Ha = 0, 10, 20 and phi = 0, 0.02, 0.04, respectively. Analysis was carried out with the ANSYS Fluent commercial software. Fluid velocity curves, local Nusselt (Nu(X)) and average Nusselt (Nu) values are presented graphically. In all Re numbers, the fluid velocity decreases with magnetic field strength and nanoparticle effect. Local Nu number has increased with magnetic field, nanoparticle volume fraction (Re = 500) and Re number. However, this increase is less for the nano-fluid volume fraction, and then decreases at Re = 5 and 50. At all magnetic field strengths, the mean Nu number for Re = 5 and 50 is reduced with the addition of nanoparticles, but has increased for Re = 500. At all nano-volume fraction, the average Nu number is increased with the magnetic field for Re = 50 and 500. For Re = 5, the average Nu number increases up to Ha = 10, but it decreases at Ha = 20. As a result, magnetic field strength, nano-fluid volume fraction and Re number have found to be effective on heat transfer, and nano-fluid motion can be controlled by magnetic field.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: Nano-fluid; Magnetohydrodynamic; Forced convection; Pipe